2018
DOI: 10.1111/jre.12554
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐3064‐3p regulates the differentiation of cementoblasts through targeting DKK1

Abstract: This study demonstrates, for the first time, that miR-3064-3p suppresses cementoblast differentiation via the regulation of DKK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
1
18
2
Order By: Relevance
“…Therefore, these miRNAs can work in concert and efficiently during cementoblast commitment by interacting with each other. Some groups have reported the role of microRNAs in cementogenesis [50][51][52] ; however, in this study, we did not detect the same mRNAs and microRNAs as those detected in previous reports. Taking into consideration that double overexpression of miR-383 and miR-628-5p weakened the enhancement of CEMP1…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, these miRNAs can work in concert and efficiently during cementoblast commitment by interacting with each other. Some groups have reported the role of microRNAs in cementogenesis [50][51][52] ; however, in this study, we did not detect the same mRNAs and microRNAs as those detected in previous reports. Taking into consideration that double overexpression of miR-383 and miR-628-5p weakened the enhancement of CEMP1…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, these miRNAs can work in concert and efficiently during cementoblast commitment by interacting with each other. Some groups have reported the role of microRNAs in cementogenesis 50‐52 ; however, in this study, we did not detect the same mRNAs and microRNAs as those detected in previous reports. Taking into consideration that double overexpression of miR‐383 and miR‐628‐5p weakened the enhancement of CEMP1 and OPN mRNA expression (Figure 2), cementogenesis of MSCs likely regulates some factors, for example, Nfat5, DKK1, miR‐361‐3p, miR3064‐3p, or miR‐155‐3p, and the underlying mechanisms must be elucidated.…”
Section: Discussioncontrasting
confidence: 94%
“…Cementoblasts, root lining cells, share similar features with osteoblasts, such as the expression of bone-associated markers, including Osterix, OCN, and BSP 29. Previous studies by our group manifested many molecules generated during cementogenesis like osteogenic markers and microRNAs are beneficial for regeneration 25, 30-32. Therefore, obtaining insights into tissue regeneration requires further understanding on the reconstruction of impaired cementum upon bacterial invasion.…”
Section: Discussionmentioning
confidence: 95%
“…To fully understand the expression patterns and biological roles of miRNAs in cementoblast differentiation, we previously performed miRNA microarray profiles during cementoblast differentiation in vitro (Wang, Liao, et al 2018). We also observed that miR-3064-3p persistently decreased during cementoblast differentiation and regulated cementoblast differentiation through targeting Dickkopf-related protein 1 (DKK1).…”
Section: Introductionmentioning
confidence: 99%